Sonic hedgehog is Essential for Proximal-Distal Outgrowth of the Limb Bud in Salamanders - Purushothaman, Sruthi; Lopez Aviña, Brianda B.; Seifert, Ashley W. (Frontiers in Cell and Developmental Biology, 2022)
The developing forelimb has been a foundational model to understand how specified progenitor cells integrate genetic information to produce the tetrapod limb bauplan [1; 2]. Although the reigning hypothesis is that all tetrapods develop limbs in a similar manner, recent work suggests that urodeles have evolved a derived mode of limb development [3; 4; 5]. Here we demonstrate through pharmacological and genetic inactivation of Sonic hedgehog (Shh) signaling in axolotls that Shh directs expansion and survival of limb progenitor cells in addition to patterning the limb across the proximodistal and antero-posterior axis. In contrast to inactivation of Shh in mouse or chick embryos where a humerus, radius and single digit develop [6; 7; 8; 9], Shh crispant axolotls completely lack forelimbs. In rescuing limb development by implanting SHH-N protein beads into the nascent limb field of Shh-crispants, we show that the limb field is specified in the absence of Shh and that hedgehog pathway activation is required to initiate proximodistal outgrowth. When our results are examined alongside other derived aspects of salamander limb development and placed in a phylogenetic context, a new hypothesis emerges whereby the ability for cells at an amputation plane to activate morphogenesis and regenerate a limb may have evolved uniquely in urodeles.